Communication about noxious weeds among property owners in Teton County, Wyoming - Parker-Renga, Theodore P., author; Hallahan, Kirk, advisor; Champ, Joseph G., committee member; Fernandez-Gimenez, Maria E., committee member (Colorado State University. Libraries, 2013)
A survey, conducted in cooperation with the Teton County Weed & Pest District, was mailed to property owners (n = 414) in Teton County (Jackson Hole), Wyoming, to explore how and why this audience seeks information about noxious weeds. Prior to the survey, a model was developed based on concepts and relationships adapted from the Risk Information Seeking and Processing model (Griffin, Dunwoody, & Neuwirth, 1999). High levels of concern about the risk posed by weeds, coupled with a low perceived knowledge, were correlated with the need for information about this topic. Consistent with the RISP model, the likelihood of seeking information was highly correlated with perceived social pressure to be informed about invasive plants. However, information need as measured here, which varied from the approach used in the RISP model, was negatively correlated to information seeking, suggesting that self-identity, or a sense of duty to others or the community, might better explain information seeking. Perceived knowledge was related to a higher frequency of controlling weeks (defined as 3 or more times a year), whether the respondent worked in a weed-related industry, and membership (versus non-membership) in a conservation organization. Concern was mostly explained by frequency of controlling weeds. Perceived social pressure to be informed was driven by owning a larger parcel (>1 acre), by working in a weed-related industry, and by membership in a conservation organization. A higher frequency of controlling weeds was the best predictor of information seeking, while owning more than 1 acre, working in a weed-related industry, and membership in a conservation organization were predictors of information sharing. No statistically significant differences were discerned based on gender. Property owners, who were notably older (mean age of 58 years) and better educated (73.3% completed college) than the American population as a whole, indicated brochures and websites as the tools they prefer for learning and sharing information about weeds. Little support was found for using social media, such as Facebook, for spreading the word about weeds among property owners. Participants did report a strong willingness, however, to share information with family, friends, and neighbors, suggesting social networks do have potential for disseminating information about invasive plants. Property owners expressed a need to know more about control options other than herbicides and for help with identification. While they had only a moderate concern about weeds in general, property owners did express a high level of concern for the negative impacts weeds pose to desirable vegetation. Practical implications for communicating about noxious weeds with property owners are discussed.
Keywords: information seeking; information sharing; invasive plants; noxious weeds; risk communication; Teton County (Jackson Hole)